Use of alteplase continuous rate infusion, pentoxifylline, and cyproheptadine in association or not, in acute feline aortic thromboembolism: a study of nine cats - Ray, Christopher C.; Wolf, Jacob; Guillaumin, Julien (Frontiers in Veterinary Science, 2025)
IntroductionLocomotion improvement without serious complications is the main goal of treatment for feline aortic thromboembolism (FATE). We aimed to describe the survival and functional recovery of cardiogenic FATE treated with tissue plasminogen activator (rtPA) continuous rate infusion (CRI) and/or pentoxifylline (PTX) and/ or cyproheptadine (CYP), and to identify non-survivor characteristics.MethodsThis is a retrospective, bicentric case series. Inclusion criteria were cardiogenic FATE cats receiving any of the medications described. Proportions of locomotion recovery, survival to discharge, reperfusion injury (RI) and acute kidney injury (AKI) were described. Admission and outcome characteristics were compared between survivors and non-survivors.ResultsNine cats were identified, 8/9 (88.9%) with bilateral FATE. Median age was 8.2 years (5.3–12.5). Median weight was 5.3 kg (4.1–7.1). Admission rectal temperature, affected limb lactate, creatinine and potassium were 36.9°C (35.4–38.8), 14.2 mmol/L (7.1–18.8), 114.9 umol/L (53–185.6) and 3.7 mmol/L (3.5–44.), respectively. No significant differences were found between survivors and non-survivors for relevant admission characteristics. Seven (77.8%) cats received tPA-CRI, 7/9 (77.8%) cats received pentoxifylline and 5/9 (55.6%) cats received cyproheptadine. Three (33.3%) cats received monotherapy (two rtPA-CRI, one PTX), 2/9 (22.2%) cats received dual therapy (one rtPA-CRI/PTX, one PTX/ CYP) and 4/9 (44.4%) cats received triple therapy. All study cats (100%) had an improvement in locomotion, and 4/9 (44.4%) survived to discharge. Reperfusion injury and AKI were documented in 3/9 (33.3%) and 4/9 (44.4%) of cats, respectively. Non-survivors had a greater proportion of AKI than survivors (4/5 (80%) and 0/4 (0%), respectively). No other outcome characteristics were different between survivors and non-survivors.DiscussionrtPA CRI, PTX and/or CYP could be considered for treatment of FATE.